Effectiveness of digital media in increasing knowledge of e-cigarettes - Ridwan, M.; Noerjoedianto, Dwi; Halim, Rd. (Proceedings Academic Universitas Jambi, 2025)
Background: E-cigarette education must be carried out differently from conventional cigarette education. E-cigarettes are growing and developing at a time when the digital world is the main communication channel today. Objective: The purpose of this study is to determine the effectiveness of media in gital with websites to remind adolescents of knowledge and attitudes about e-cigarettes. Method: The research method used is qualitative with a case study approach. The research informants were 20 high school students. Data collection using in-depth interviews. The data analyst used the Milles and Hyberman methods. Results: The results of this study show that most users are very easy to access applications and want to try using them. Web applications make it easier to understand the material that is broadcast because it is in the form of images and sounds. The informant’s knowledge can be measured after conducting a pre and post test. Conclusion: The media on the website is very effective in increasing the knowledge of the user in understanding the material of E-cigarettes